Elasticities of Turkish Exports and Imports - Ayla Oğuş Binatlı; Niloufer Sohrabji (Izmir University of Economics, Department of Economics, 2009)
The Turkish current account has been exploding in the last few years leading to concerns of a crisis. One of the primary factors identified in the rising deficits is the appreciating lira. In addition, income elasticity of exports and imports can also shed light on continuing trade deficits. In this paper we analyze exchange rate and income elasticity of Turkish imports and exports. We find a significant gap between domestic and foreign income elasticities (for exports and imports respectively) which points to a threat of growing trade deficits. In addition we also find that the exchange rate elasticity is negative for both Turkish exports and imports. This indicates that depreciation of the Turkish lira will have a negative effect on both imports and exports.
Keywords: F32; F41; 330; Cointegration; current account deficits; exchange rate and income elasticity; Turkey; Import; Export; Einkommenselastizität der Nachfrage; Wechselkurs; Außenwirtschaftliches Gleichgewicht; Türkei